2017
DOI: 10.1111/vde.12470
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the effect of pullulan‐conjugated Der f 2 allergen‐specific immunotherapy on canine atopic dermatitis

Abstract: The results indicate the effectiveness of Der f 2-P recombinant protein in the treatment of dogs with CAD and testing positive to D. farinae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
(29 reference statements)
0
22
1
Order By: Relevance
“…This response rate is similar to previous studies on subcutaneous and intralymphatic ASIT using crude Df extracts. A previous study reported an even higher response rate in 84.6% (11 of 13) of treated dogs, but in that study the clinical criteria as well as study length were different from our study, and a direct comparison with our data is therefore difficult . However, similar to that study, in 47% of our cases withdrawal of immunomodulating medications was possible.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This response rate is similar to previous studies on subcutaneous and intralymphatic ASIT using crude Df extracts. A previous study reported an even higher response rate in 84.6% (11 of 13) of treated dogs, but in that study the clinical criteria as well as study length were different from our study, and a direct comparison with our data is therefore difficult . However, similar to that study, in 47% of our cases withdrawal of immunomodulating medications was possible.…”
Section: Discussioncontrasting
confidence: 82%
“…In agreement with a previous study there was no correlation between the sensitization pattern (polysensitized vs . monosensitized) and treatment outcome . Of the five dogs which were positive only to Df and As, two showed an excellent response, one showed a good response, one a fair response and one was classified as a treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further and comparative studies are also needed to investigate which alternative application route is most suitable in which clinical situation. Using recombinant allergens such as Dermatophagoides farinae allergen (Der f 2) [ 149 , 150 ] may result in more reproducible results and a higher success rate compared to standard AIT and ILIT [ 151 ]. Modified allergen preparations such as allergoids, allergen peptides as well as alteration with adjuvants may decrease the risk of adverse effects and increase efficacy [ 152 ].…”
Section: Unmet Needs and Researchmentioning
confidence: 99%
“…Mannan-dextran-maltodextrin covalently attached to OVA and papain were intradermally injected into BALB/c mice, leading to elevated humoral immune responses, and an IgE-to-IgG-shift ( 43 ). Another potentially useful polysaccharide is pullulan, a polysaccharide which, coupled to HDM allergen Der p 2, and administered to dogs, effectively reduced clinical signs of atopic dermatitis ( 44 ). Carbohydrate-modified ultrafine ceramic-core based nanoparticles, so-called aquasomes, are not biodegradable, and have been applied in the mouse model with ovalbumin (OVA) as model allergen preparation for intradermal application ( 45 ).…”
Section: Allergens Administered With Novel Adjuvantsmentioning
confidence: 99%